Gyrokinetic simulations of particle transport in pellet fuelled JET discharges. (11th August 2017) - Tegnered, D; Oberparleiter, M; Nordman, H; Strand, P; Garzotti, L; Lupelli, I; Roach, C M; Romanelli, M; Valovič, M
Abstract: Pellet injection is a likely fuelling method of reactor grade plasmas. When the pellet ablates, it will transiently perturb the density and temperature profiles of the plasma. This will in turn change dimensionless parameters such as a / L n, a / L T and plasma β . The microstability properties of the plasma then changes which influences the transport of heat and particles. In this paper, gyrokinetic simulations of a JET L-mode pellet fuelled discharge are performed. The ion temperature gradient/trapped electron mode turbulence is compared at the time point when the effect from the pellet is the most pronounced with a hollow density profile and when the profiles have relaxed again. Linear and nonlinear simulations are performed using the gyrokinetic code GENE including electromagnetic effects and collisions in a realistic geometry in local mode. Furthermore, global nonlinear simulations are performed in order to assess any nonlocal effects. It is found that the positive density gradient has a stabilizing effect that is partly counteracted by the increased temperature gradient in the this region. The effective diffusion coefficients are reduced in the positive density region region compared to the intra pellet time point. No major effect on the turbulent transport due to nonlocal effects are observed.